Abstract of a Study of Small and Medium Industries in Sarawak/ Dr. Ibrahim Shah ... [et al.] - Shah, Ibrahim; Amin, Nicholas; Yin, Yap; Seh Ling, Iris Syawe (Institut Teknologi MARA Cawangan Sarawak, 1991)
Since her independence some 27 years ago, Sarawak has always been keen to be on par (at the industrial level) with her Malaysian counterparts. Towards this direction, the State Government has provided various incentives and assistance especially to the small and medium scale industries due to their role in creating job opportunities and improving income distribution between the rural and urban areas in the State. Sarawak is also fortunate because she is well-endowed with rich natural resources. These must be properly tapped and utilized to provide growth and economic progress in the State. Hence, industrialization can help to complement the overall development of the State. The study attempts to provide a clear scenario ofthe manufacturing establishments in terms oftheir profile, production, marketing, manpower and training. It also provides insight into the entrepreneurs profile, the impact of the stimulatory assistance or services and the problems faced by the Small and Medium Industries (SMIs).